KEWENANGAN DESA DALAM PENATAAN RUANG BERDASARKAN UNDANG-UNDANG DESA - Femilia, Yessyca; Huda, Uu Nurul (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2020)
Abstrct This research is in the background by article 69 paragraph (4) of Law No. 6 of 2014 about Village Juncto Article 8 Regulation of the Minister of Villages, development of disadvantaged regions, and transmigration number 1 year 2015 about the Authority guidelines based on rights of origin and local authority of the village scale that gives authority to the village to arrange its own space based on the right of origin Although this rule has long been applied, in fact it is very rare that villages make village regulations on spatial planning. Village authority in the arrangement of space implemented based on the right of origin of the village and local authority of the village scale arranged in reference to the village's Medium term development plan (RPJM Des), the Village development work plan (RKP Des). This authority is the original authority mandated by the village LAW. This authority has not been effective due to lack of human resources; No technical guidance to the village government; The amount of budget required; And the absence of regulations governing the authority of the village and the mechanism for the arrangement of rural spaces is clearer. The arrangement of this Regulation in fact is difficult to implement because there is no technical guidance on the village government because the district government considers the village does not need its own space arrangement; The absence of coordination with the District government; and unavailability of human resources. The authority of this village room arrangement can accommodate the aspirations of the village community in accordance with local culture but if the coordination is not going well it will cause various problems. Abstrak Penelitian ini dilatar belakangi oleh Pasal 69 ayat (4) Undang-Undang Nomor 6 Tahun 2014 tentang Desa juncto Pasal 8 Peraturan Menteri Desa, Pembangunan Daerah Tertinggal, dan Transmigrasi Nomor 1 Tahun 2015 tentang Pedoman Kewenangan Berdasarkan Hak Asal Usul dan Kewenangan Lokal Berskala Desa yang memberikan kewenangan kepada desa untuk mengatur penataan ruangnya sendiri berdasarkan hak asal usul dan kewenangan lokal berskala desa. Meskipun peraturan ini sudah lama diterapkan, nyatanya sangat jarang sekali desa yang membuat peraturan desa mengenai tata ruang. Kewenangan desa dalam penataan ruang dilaksanakan berdasarkan hak asal usul desa dan kewenangan lokal berskala desa yang disusun mengacu pada Rencana Pembangunan Jangka Menengah Desa (RPJM Des), Rencana Kerja Pembangunan Desa (RKP Des). Kewenangan ini merupakan kewenangan asli yang diamanatkan oleh UU Desa. Kewenangan ini belum berjalan efektif karena kurangnya sumber daya manusia; belum adanya bimbingan teknis terhadap pemerintah desa; besarnya anggaran yang dibutuhkan; serta belum adanya peraturan yang mengatur kewenangan desa dan mekanisme penyusunan penataan ruang desa yang lebih jelas. Penyusunan peraturan ini nyatanya sulit dilaksanakan karena belum adanya bimbingan teknis terhadap pemerintah desa karena pemerintah kecamatan menganggap desa belum memerlukan pengaturan ruangnya sendiri; belum adanya koordinasi bersama pemerintah kabupaten; dan tidak tersedianya sumber daya manusia. Kewenangan penataan ruang desa ini dapat menampung aspirasi masyarakat desa sesuai dengan budaya lokalnya akan tetapi jika koordinasi tidak berjalan dengan baik maka akan menimbulkan berbagai permasalahan.